5‐2: Invited Paper: Ultrathin Stretchable Oxide Thin Film Transistor and Active Matrix Organic Light‐Emitting Diode Displays. Issue 1 (2nd June 2017) - Ahn, Seong-Deok; Kang, Seung-Youl; Cho, Sung-Haeng; Yang, Jong-Heon; Lee, Hyunkoo; Na, Bock-Soon; Koo, Jae-Bon; Park, Chan-Woo; Byun, Chun-Won; Kwon, Byoung-Hwa; Cho, Nam-Sung; Hwang, Chi-Sun; et al.
Abstract : We demonstrate ultrathin (2 µm thick) stretchable oxide thin film transistor and active matrix organic light‐emitting diode displays. They can be operated as free‐standing ultrathin films under 10% strain. Stretchable active matrix organic light‐emitting diode displays are becoming increasingly important the applications fields of large‐area stretchable displays, wearable displays, electronic skin devices.